Nicotine Addiction: Neurobiology and Mechanism - Raj Kumar Tiwari; Vikas Sharma; Ravindra Kumar Pandey; Shiv Shankar Shukla (Korean Pharmacopuncture Institute, 2020)
Nicotine, primary component of tobaco produces craving and withdrawal effect both in humans and animals. Nicotine shows a close resemblance to other addictive drugs in molecular, neuroanatomical and pharmacological, particularly the drugs which enhances the cognitive functions. Nicotine mainly shows its action through specific nicotinic acetylcholine receptors located in brain. It stimulates presynaptic acetylcholine receptors thereby enhancing Ach release and metabolism. Dopaminergic system is also stimulated by it, thus increasing the concentration of dopamine in nuclear accumbens. This property of nicotine according to various researchers is responsible for reinforcing behavioral change and dependence of nicotine. Various researchers have also depicted that some non dopaminergic systems are also involved for rewarding effect of nicotinic withdrawal. Neurological systems such as GABAergic, serotonergic, noradrenergic, and brain stem cholinergic may also be involved to mediate the actions of nicotine. Further, the neurobiological pathway to nicotine dependence might perhaps be appropriate to the attachment of nicotine to nicotinic acetylcholine receptors, peruse by stimulation of dopaminergic system and activation of general pharmacological changes that might be responsible for nicotine addiction. It is also suggested that MAO A and B both are restrained by nicotine. This enzyme helps in degradation dopamine, which is mainly responsible for nicotinic actions and dependence. Various questions remain uninsurable to nicotine mechanism and require more research. Also, various genetic methods united with modern instrumental analysis might result for more authentic information for nicotine addiction.